Institutionalization of Gender Mainstreaming in Regional Development Planning and Budgeting in East Kalimantan Province - Nadia Istamala; Muh. Jamal Amin; Cathas Teguh Prakoso (CV. Social Politic Genius (SIGn), 2026)
Gender mainstreaming in regional development requires institutionalization that connects role distribution, implementer capacity, and instrument use within planning and budgeting processes. This study analyzes the institutionalization of gender mainstreaming in East Kalimantan Province through institutional coordination, implementer capacity, and the use of gender-responsive planning and budgeting instruments. This field study employed a qualitative descriptive approach and was conducted from February to June 2026. Data were collected through in-depth interviews with purposively selected informants, observations, and document review. The analysis involved thematic grouping and cross-checking across data sources and data collection methods. The findings show that implementation structures and coordination activities have been established, but operational responsibilities remain dominated by the East Kalimantan Provincial Office of Women’s Empowerment and Child Protection. Capacity development has been implemented, while gender analysis skills and the ability to prepare Gender Budget Statements remain unevenly distributed. The implementation of gender-responsive planning and budgeting instruments has established an administrative sequence involving Klik SiGen, gender-responsive budget compilation, and reporting. Integration of these instruments with program and budget decisions remains inconsistent. These three elements produce an empirical pattern of institutionalization dominated by the Office of Women’s Empowerment and Child Protection as the driving organization. This pattern results from mutually reinforcing relationships among uneven role distribution, uneven capacity distribution, and dependence on assistance in instrument use.